Exogenous biostimulant bee-honey solution improves Triticum aestivum L. tolerance to salt stress by modulating physio-biochemical responses and upregulation of salinity-related genes - Algasem, Asma; Alghamdi, Sameera; Alsamadany, Hameed (Frontiers in Plant Science, 2026)
IntroductionSalinity is a major global constraint to wheat productivity, primarily due to oxidative damage, osmotic imbalance, and ionic toxicity. This study evaluated the potential of bee-honey solution (BHS) as a natural biostimulant to mitigate salinity stress effects in wheat (cv. Yecora Rojo).MethodsPlants were treated with 0, 100, 150, and 200 mM NaCl, with foliar application of BHS (0, 1.0, and 1.5%). BHS potential influences on plant growth, physio-biochemical indices, antioxidant defense system, and gene expression under four salinity levels were evaluated.ResultsSalt stress at 200 mM, decreased plant height by 25%, leaf area by 14%, and biomass by 28% compared to control, while chlorophyll content reduced by 63%, and the Na+/K+ ratio rose by 206%. Besides, ROS levels inclined markedly, with H2O2 (+ 125%), O2•− (+ 100%), and MDA (+ 129%) accumulation relative to non-stressed plants. Foliar application of BHS, particularly at 1.5%, significantly mitigated these effects: plant height increased by 37%, leaf area by 43%, and biomass by 52% compared to stressed-control plants. Chlorophyll content increased by 73%, RWC rose by 25%, and the Na+/K+ ratio decreased by 23%. Besides, BHS significantly reduced H2O2 (- 17%), O2•− (- 18%), and MDA (- 31%) levels while increasing antioxidant enzyme activities: SOD (+ 33%), POD (+ 86%), and CAT (+ 38%). Proline content increased by 25% through TaP5CS upregulation, while GB decreased by 29%, indicating regulated osmolytic balance. Gene expression analysis showed strong upregulation of TaPOD-D1 (+ 4.1-fold), TaSOD2 (+ 3.8-fold), TaCAT1 (+ 3.6-fold), TaNHX2 (+ 2.9-fold), and TaHKT1;4 (+ 3.2-fold) in BHS-treated plants under salt stress. Multivariate analyses; PCA and heatmap confirmed close association of BHS treatments with increased physiological, biochemical, and molecular responses, particularly under high salinity level.Discussion & conclusionThe present findings prove that BHS is an effective, eco-friendly biostimulant that imparts salt resilience to wheat by integrating morphological, physiological, biochemical, and molecular mechanisms.